2016
DOI: 10.1177/1933719116630421
|View full text |Cite
|
Sign up to set email alerts
|

Expression and Regulation of Pituitary Adenylate Cyclase-Activating Polypeptide in Rat Placental Cells

Abstract: Pituitary adenylate cyclase-activating polypeptide (PACAP) was first identified as a hypophysiotropic factor that regulates pituitary cell functions and has been subsequently shown to be widely distributed and have multiple functions. The PACAP is known to be expressed in placental tissues and is suggested to have a critical role in physiological function of the placenta. In addition to PACAP, the hypothalamic peptides kisspeptin and gonadotropin-releasing hormone (GnRH) are also expressed in placental cells. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 36 publications
1
8
0
Order By: Relevance
“…This finding is consistent with that reported by Horikoshi et al 9 However, a positive correlation between KP-10 and β-hCG was noticed during the 3rd trimester in PE women. A finding that was also noticed by other researchers Oride et al 10 who reported the stimulatory effect of kisspeptin on hCG mRNA expression in rat placental cells. Therefore, it is noteworthy that rapidly rising β-hCG concentrations during pregnancy suppress secretion of both LH and FSH by blunting the response to gonadotropin-releasing hormone (GnRH).…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…This finding is consistent with that reported by Horikoshi et al 9 However, a positive correlation between KP-10 and β-hCG was noticed during the 3rd trimester in PE women. A finding that was also noticed by other researchers Oride et al 10 who reported the stimulatory effect of kisspeptin on hCG mRNA expression in rat placental cells. Therefore, it is noteworthy that rapidly rising β-hCG concentrations during pregnancy suppress secretion of both LH and FSH by blunting the response to gonadotropin-releasing hormone (GnRH).…”
Section: Discussionsupporting
confidence: 87%
“…Likewise, expression of KP-10 mRNA has been observed to be augmented in both human and rat placenta. 9,10 High concentrations of KP-10 have been found in syncytiotrophoblasts, which secrete several hormones. This includes, human chorionic gonadotropin (hCG), placental growth hormone, estrogen (E2) and progesterone (PRG).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We further identified one fetal locus associated with maternal sIL2R-α, ADCYAP1 , or PACAP , which encodes a signalling neuropeptide widely expressed in the central and peripheral nervous systems. PACAP is also expressed in different parts of the placenta and the umbilical cord where it affects cell survival, angiogenesis, and proliferation of trophoblast cells [ 58 ]. This locus was not associated with any fetal cytokine/chemokine, nor has it previously been associated with adult immune phenotypes [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…The most likely option is that PACAP originates from the placenta because PACAP immunoreactive fibers innervate vessels in the uteroplacental unit in humans (151). PACAP38 and PAC1 mRNA has been demonstrated in the placenta as well as immunoreactive stromal and decidual cells in humans and rats (152)(153)(154)(155).…”
Section: Pacap In Plasmamentioning
confidence: 99%